The Effect of Video Content Generation on Pre-Service English Teachers’ Speaking Anxiety, Self-Efficacy, and Willingness to Communicate - Yuruk, S. Eren; Yilmaz, Rabia M. (Ozgen Korkmaz, 2025)
The study examines the effects of video content generation activities on EFL pre-service English language teachers’ foreign language speaking anxiety, perceived speaking self-efficacy, and willingness to communicate. The study used a sequential explanatory design of mixed research methods. In the quantitative phase of the study, a quasiexperimental design with a pretest-posttest control group was used, while the qualitative phase employed a case study approach. The quantitative phase of the study was conducted with 30 experimental and 32 control group students. The study employed the Foreign Language Speaking Anxiety Scale, the Speaking Skills Self-Efficacy Belief Scale, and the Instructional Willingness to Communicate Scale as data collection instruments. The data were analyzed using the ANCOVA test. In the qualitative phase, focus group interviews were conducted with 17 students from the experimental group using a semi-structured interview form. After eight weeks of implementation, moderately significant differences were found in favor of the experimental group on speaking. According to the qualitative findings, the participants attributed the observed changes in their motivation to frequent repetition, an increased sense of achievement in their knowledge and skills during the process, the presence of an online audience, and the development of in-class interactions. They also stated that the application fostered an environment conducive to assessment and feedback through online interactions. © 2025, Ozgen Korkmaz. All rights reserved.
Keywords: foreign language speaking anxiety; speaking self-efficacy; video content generation; willingness to communicate